Risk factors for anaemia among pregnant women: A cross-sectional study in Upper East Region, Ghana. - Clotilda Asobuno; Silas Adjei-Gyamfi; Felix Gumaayiri Aabebe; John Hammond; Chansathit Taikeophithoun; Norbert Ndaah Amuna; Tsunenori Aoki; Hirotsugu Aiga (PLoS ONE)
Background Anaemia in pregnancy (AIP) is a public health concern due to its devastating effects on women and their unborn babies, resulting in increased maternal and neonatal deaths in developing countries. Despite several Ghanaian health policies to combat AIP, AIP is still on the rise. It becomes imperative to identify geographic-specific factors for developing appropriate interventions for the management of AIP. However, Kassena Nankana West District (KNWD) in the Upper East Region of Ghana lacks a study on anaemia risk factors, therefore, this study estimated the prevalence and risk factors for anaemia among pregnant women in the district. Methods A cross-sectional study was conducted from February to March 2023 in the KNWD. Approximately 376 pregnant women in their third trimester were randomly selected from 10 health facilities by utilizing the antenatal register as the sampling frame. Anthropometric, obstetric, sociodemographic, and health facility resource characteristics were collected using structured questionnaires and from antenatal records. Mixed-effect logistic regression was used to identify independent factors of anaemia at 95% confidence interval. Results Prevalence of AIP was 53.9% (95%CI:48.5%-58.8%). Mild, moderate, and severe anaemia prevalence was 16.9%, 35.3%, and 1.7% respectively. Malaria infection during pregnancy (aOR = 1.64; 95%CI:1.03-2.62) and accessing health facilities without trained laboratory personnel (aOR = 5.49; 95%CI:1.67-18.00) were associated with increased odds of AIP. Belonging to the major ethnic group (aOR = 0.52; 95%CI:0.28-0.85), accessing health facilities without laboratory services (aOR = 0.14; 95%CI:0.04-0.47), and accessing health facilities without sulphadoxine-pyrimethamine drugs (aOR = 0.22; 95%CI:0.06-0.86) in KNWD were also associated with decreased odds of AIP. Conclusion KNWD has a severe burden of AIP. Maternal and health facility-related factors were associated with AIP in the district. These factors are preventable. Therefore, the provision of functional laboratory services with dedicated technical personnel, regular supply of sulphadoxine-pyrimethamine drugs to the health facilities, and enhanced community education on malaria prevention are recommended for anaemia control in the district.